Desenvolvimento de plântulas de cajueiro anão sob diferentes níveis de adubação e submetidas à diferentes níveis de salinidade - Paiva, Thamiris Ferreira Pinto (2018)
Salinity is one of the main problems faced by irrigated agriculture in the semiarid. Several strategies have been used for the purpose of mitigating this damage. These strategies include the soil corrections and genetic improvement to obtain genotypes more resistant. Thus, the present work aimed to study fertilization effects on the rootstocks formation and the development of dwarf cashew seedlings, irrigated with different levels of salinity water. Two experiments were carried out at Embrapa Agroindústria Tropical (Fortaleza - CE). In the first experiment, treatments resulted from the combination between three cashew clones (CCP 06, CCP 76 and EMBRAPA 51) and three fertilization levels with NPK (control - no fertilization, 50% and 100% of the conventional nutrition used by the crop), it was incorporated to the substrate before sowing. 30 and 60 days after sowing the parameters of seed emergence, seedling growth and leaf nutrient content were evaluated. In the second experiment, treatments resulted from the combination between three fertilization levels with NPK (the same ones used in the first experiment) and four saline irrigation water levels (ECw: 0.8, 4.0, 7.0 and 10.0 dS m-1). Gas exchange, photoassimilates accumulation, growth and nutrient content in leaves, stems, and roots of seedlings were evaluated at 90 days after grafting. In relation to the first experiment results, fertilization levels did not exert significant effects on the evaluated parameters. Differentiated responses were due to the genotypic characteristics of each clone studied. The CCP76 clone presented the highest precocity of emergence than CCP06 and Embrapa51 clone. The three clones studied were able to be used as rootstocks. In the second experiment, fertilization levels had a little influence on the seedlings growth, in general, showing a tendency to reduce growth at the maximum fertilization level. The BRS 189 clone grafted on the CCP 06 clone was tolerant to a ECw of approximately 7.0 dS m-1. The fertilization did not interfere in the photoassimilates production, which showed a better performance when the seedlings were submitted to a salinity 7.0 dS m-1. The NPK application to the substrate provided higher nitrogen levels in leaves, while the phosphorus had lower contents and the leaf potassium was not influenced by fertilization.